The Detection of the Rise to Stand Movements Using Bereitschaftspotential from Scalp Electroencephalography (EEG) - Balbir Singh; Hiroaki Wagatsuma; Kiyohisa Natsume (SICE Journal of Control, Measurement, and System Integration, 2017)
The negative-going Bereitschaftspotential (BP) is associated with the preparation and execution of dynamic movement. So far, BP for simple movements involving either the upper or the lower body has been studied. However, BP has not yet been recorded during both movements. Our study reveals that the negative-going BP was evoked around 3 to 2 seconds before the onset of the rise in response to a start cue. The BP had a negative peak before the onset of the movement of the trunk. BP for the rise to standing up was started around -3 seconds. The corresponding BP while seated could not be recorded in response to the other start cue. Then we tried to discriminate the onset for rise to stand, and for keeping seated using BP data in time domain. BP for 0.5 seconds in the time window is used for the time-shifted leave-one-out cross validation method. The method shows that using 0.5 seconds to 2 seconds before the onset of the movement could detect whether the subject would stand up or keep seated with the correction rate of about 60% to 70%. These results suggest that using the negative BP can detect the subject's will to stand-up.